ANALISIS REGRESI NONPARAMETRIK SPLINE MULTIVARIAT UNTUK PEMODELAN INDIKATOR KEMISKINAN DI INDONESIA - ASTITI, DESAK AYU WIRI; SUMARJAYA, I WAYAN; SUSILAWATI, MADE (E-Jurnal Matematika; Vol 5 No 3 (2016)DO - 10.24843/MTK.2016.v05.i03.p129, 2016)
The aim of this study is to obtain statistics models which explain the relationship between variables that influence the poverty indicators in Indonesia using multivariate spline nonparametric regression method. Spline is a nonparametric regression estimation method that is automatically search for its estimation wherever the data pattern move and thus resulting in model which fitted the data. This study, uses data from survey of Social Economy National (Susenas) and survey of Employment National (Sakernas) of 2013 from the publication of the Central Bureau of Statistics (BPS). This study yields two models which are the best model from two used response variables. The criterion uses to select the best model is the minimum Generalized Cross Validation (GCV). The best spline model obtained is cubic spline model with five optimal knots.
Keywords: Nonparametrik, Spline, multivatiat, indikator kemiskinan